2006
DOI: 10.2205/2006es000194
|View full text |Cite
|
Sign up to set email alerts
|

Crustal velocity structure under the RUKSA seismic array (Karelia, Russia)

Abstract: Based on data of three three-component seismographs belonging to the temporary smallaperture Russian Karelia Seismic Array (RUKSA) in the Petrozavodsk region (Karelia), a 1-D velocity model of the crust is constructed by the method of the receiver function. Waveforms of distant earthquakes recorded by short-period instruments with improved characteristics are used. The data were inverted by the simulated annealing method. The inversion was stabilized by using phase velocities of Rayleigh waves and traveltimes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 15 publications
(17 reference statements)
0
16
0
Order By: Relevance
“…12a). The same layer was revealed also beneath APA and LVZ stations in the Kola Peninsula (Dricker et al 1996) and beneath RUKSA array (Aleshin et al 2006). The layer has not been revealed either by previous controlled‐source experiments or by local event studies based on body waves (Hyvönen et al 2007), although this layer has been indicated by the analysis of surface waves from quarry blasts and shots registered during the SVEKA wide‐angle refraction and reflection experiment (Pedersen & Campillo 1991; Grad & Luosto 1994).…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…12a). The same layer was revealed also beneath APA and LVZ stations in the Kola Peninsula (Dricker et al 1996) and beneath RUKSA array (Aleshin et al 2006). The layer has not been revealed either by previous controlled‐source experiments or by local event studies based on body waves (Hyvönen et al 2007), although this layer has been indicated by the analysis of surface waves from quarry blasts and shots registered during the SVEKA wide‐angle refraction and reflection experiment (Pedersen & Campillo 1991; Grad & Luosto 1994).…”
Section: Resultsmentioning
confidence: 67%
“…Introduction into the inversion of traveltime of the P ‐wave converted from the upper boundary of mantle transition zone at a depth of 410 km ( Ps 410) has not been previously used in conventional receiver function studies. The first successful attempt was made by the authors while reconstructing the crustal structure under RUKSA seismic array using short‐period seismic data (Aleshin et al 2006).…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…10) together with available observations from the surrounding regions (Aleshin et al, 2006;Båth, 1984;FENNIA Working Group, 1998;Grad and Luosto, 1987;Komminaho and Yliniemi, 1992;Luosto et al, 1989Luosto et al, , 1990Luosto et al, , 1995Olsson, 2007;Erinchek et al, 2006;Korja et al, 2001;Korsman et al, 1999;Luosto, 1991) were used to construct an updated Moho depth map (Fig. 12a).…”
Section: Modelling Of P and S Waves And Moho Depthmentioning
confidence: 99%
“…Passive seismic experiments SVEKALAPKO (Bock et al, 2001) and POLENET/LAPNET (Kozlovskaya et al, 2006) spurred a large number of research activities that targeted the lithosphere structure of the northern part of the Baltic Shield (Bruneton et al, 2002;Alinaghi et al, 2003;Aleshin et al, 2006;Vecsey et al, 2007;Kozlovskaya et al, 2008;Uski et al, 2011;Grad and Tiira, 2012;Silvennoinen et al, 2014;Vinnik et al, 2016). A significant part of these studies is based on the receiver function technique (Alinaghi et al, 2003;Aleshin et al, 2006;Kozlovskaya et al, 2008;Grad and Tiira, 2012;Vinnik et al, 2016).…”
Section: Introductionmentioning
confidence: 99%